Mengatasi Hambatan Berbicara Mengatasi Hambatan Berbicara Bahasa Arab: Analisis Peran Paparan Langsung dari Penutur Asli - Sulasmi, Sulasmi (Journal Education And Islamic Studies, 2025)
This study aims to analyze the role of direct exposure of native speakers in overcoming barriers to speaking Arabic among students majoring in Islamic Religious Education at STIT Diniyyah Puteri Rahmah El Yunusiyyah Padang Panjang. The results of the study showed that female students who regularly listened to podcasts, movies, or cartoons in Arabic fusha with translated text tended to have better speaking skills and confidence. The methodology used is a qualitative approach with a case study design, this study involves 30 female students who are selected by purposive sampling. Data was collected through in-depth interviews, classroom observations, and documentation. Data analysis was carried out using Miles and Huberman qualitative analysis techniques. The validity of the data was tested by triangulation technique. This study suggests that higher education institutions integrate the use of Arabic-language media in the curriculum to improve students' language skills, helping to improve their pronunciation, intonation, and speaking fluency. The results of this study are expected to contribute to the development of Arabic language learning methods in higher education institutions.